2015
DOI: 10.1186/s40064-015-0890-1
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and treatment-related biomarkers associated with response to high-dose interleukin-2 in metastatic melanoma and renal cell carcinoma: retrospective analysis of an academic community hospital’s experience

Abstract: BackgroundImmunotherapy in the treatment of metastatic melanoma and renal cell carcinoma can produce durable therapeutic responses, which may improve survival. We aimed to identify clinical characteristics and biomarkers associated with response to high-dose interleukin-2 therapy (IL-2) in patients with metastatic melanoma and renal cell carcinoma treated at an academic community hospital.Patients/MethodsWe retrospectively analyzed clinical variables and biomarkers of 50 consecutive metastatic melanoma or rena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…A meta-analysis of skin rash and outcomes of NSCLC with EGFR-TKIs treatment found a significant association between skin rash and favorable outcomes. 11 In IL-2 treatment of metastatic melanoma, many studies 12,13 have shown that immunologic side effects such as vitiligo and thyroiditis correlate with good clinical response to IL-2 therapy. Furthermore, a meta-analysis of immune checkpoint inhibitor therapy in melanoma found that vitiligo (skin irAE) was significantly associated with both longer PFS and OS, 20 although thyroiditis was not in another study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of skin rash and outcomes of NSCLC with EGFR-TKIs treatment found a significant association between skin rash and favorable outcomes. 11 In IL-2 treatment of metastatic melanoma, many studies 12,13 have shown that immunologic side effects such as vitiligo and thyroiditis correlate with good clinical response to IL-2 therapy. Furthermore, a meta-analysis of immune checkpoint inhibitor therapy in melanoma found that vitiligo (skin irAE) was significantly associated with both longer PFS and OS, 20 although thyroiditis was not in another study.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy that thyroiditis, which is one of the most common immune-related adverse event (irAE), is associated with the mechanism of the antitumor effect of immunotherapy, and can be easily monitored with a thyroid function test (TFT) in a clinical setting. [8][9][10] In patients treated with several other drugs, side effects related to drug mechanisms such as skin rash after epidermal growth factor receptor tyrosine kinase inhibitor use (EGFR-TKIs) 11 or vitiligo and thyroiditis after IL-2 treatment 12,13 are associated with a good prognosis. Interestingly, Dr. Osorio et al recently reported that thyroid dysfunction after pembrolizumab in NSCLC patients was associated with longer OS in an unadjusted analysis.…”
Section: Introductionmentioning
confidence: 99%